The Brazilian tax system and Latin America: a comparative analysis - doi: 10.4025/actascihumansoc.v35i1.19734 - Paes, Nelson Leitao (2013)
Current essay is a comparative study on the tax systems of Latin American countries with special reference to the evolution of revenues, tax rates and revenue composition. The revenues of a typical Latin American country are lower than the average revenues of developed countries, with a great concentration on indirect taxation. A strong correlation between income and GDP per capita and between tax rates and revenues was confirmed, except for Corporate Income Tax. Tax load in Brazil is almost twice the Latin American average and close to that of developed countries. In the case of revenue composition, Brazil is an exception within the region´s standard since it relies less on consumption taxes and more on income taxes. It is worth mentioning that revenues from the Brazilian´s corporate income tax are relatively low within the context of its high tax rates.